Efektivitas Media Game Education Berbasis Web dalam Meningkatkkan Kemampuan Mengenal Bilangan pada Disabilitas Rungu (Single Subject Research Kelas II di SLB Negeri 2 Padang) - Jayanti, Sekar Dwi; Rahmahtrisilvia, Rahmahtrisilvia; Taufan, Johandri; Zulpiani, Mardhatilla; Irdamurni, Irdamurni (Indo-MathEdu Intellectuals Journal, 2025)
This research is based on the problems discovered by the researcher at SLB Negeri 2 Padang. A hearing-impaired student in grade II who still does not recognize numbers. This study aims to improve the ability to recognize numbers using web-based educational game media. The research uses a quantitative approach and the type of research used in this study is experimental research in the form of single subject research (SSR), with an A-B-A design. The results of the study showed that the Baseline (A) condition was carried out three times and obtained a stability presentation of 30% each. Which shows a horizontal directional trend. And in the condition of Intervention (B) which was carried out 7 times by observers and obtained an increase of 90%. Which shows an increasing trend of direction with a change level (+50) and at baseline conditions (A2) that is carried out 3 times to obtain a stable percentage of 30%, indicating a tendency to increase with the change level (+5). It can be said that there is an increase in recognizing numbers by using game education media which shows the percentage of data with an overlap of 0%. Based on the results of the study, it can be concluded that web-based game education media can improve the ability to recognize numbers in children with hearing disabilities